Thomas & friends. Extraordinary engines [videorecording (DVD)] - Awdry, W. (Universal Pictures Home Entertainment, 2017)
Excitement spreads across Sodor with the arrival of a new and unusual engine. Worrying they'll be replaced by the fast and modern Hugo; the engines fail to be good friends by not making him feel welcome. When they stop to listen, they realize that Hugo is a very special engine who truly belongs on the rails. Elsewhere things get spooky when the engines see a ghost train and Percy goes on a troll hunt. Skiff takes Sir Topham Hatt on a wild ride in search of a mermaid.